PERBANDINGAN HASIL BELAJAR FISIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVMENT DIVISION (STAD) DENGAN TWO STAY TWO STRAY (TSTS) PADA POKOK BAHASAN GERAK LURUS DI KELAS VII SMPN 117 JAKARTA - Siagian, Rianto; Astra, I Made; Budi, Esmar (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The purpose of this research is to know the differences of result physic learning between who learned using cooperative learning model type of student team achievment division (STAD) and two stay two stray (TSTS). This research is done in SMPN 117 Jakarta. This research use experiment method with posttest only control groups design. Sample were taken using technique of purposive sampling. The amount of research sample is 35 students for the first experiment class and 33 students for the second experiment class. First experiment class using cooperative learning type of STAD and second experiment class using cooperatve learning type of TSTS. The result of normality test by chi square test showed is normally distribute. The result of homogenity test by F test showed data is homogenous The average score of posttest from STAD class is 64.29 and TSTS class is 53.48. The analysis used t-test, the result of calculate tscore is 3.1, while ttable at level of significances 5% with degree of freedom (dk) = 35 + 33 – 2 = 66, that is equal to 1.668. The result of research revealed that tscore > ttable or 3.1>1.668. It shows that result of physic learning cooperative type of STAD is higher than cooperative learning type of TSTS. Kata Kunci: Comparison, Cooperative Learning Model Type of STAD, TSTS, Result of Learning.